Setting up the Basque algorithmic nation: Technological sovereignty amidst the post-COVID-19 society - Calzada, I (Telesforo Monzon eLab, 2020)
This article aims to examine the current and timely situation that has recently emerged as a result of the COVID-19 pandemic crisis by proposing a strategic wake up call in the Basque Country regarding the need to reimagine the international role of stateless nations through a not less urgent techno-political response and standpoint. Despite the fact that European cityregions presents rather distinct and unique compositions, this policy strategic analysis—centred comparatively in the Basque Country—sheds light on a potential roadmap to enhance the way digital transformations, AI, and data ecosystems/governance can provide an opportunity amidst this pandemic crisis for empowering citizens and institutions and opening up a transnational collaboration based on solidarity with other cities, regions, and nations in Europe and worldwide. Given the thorny aftermaths for many European city-regions, this article encourages particularly stakeholders in the Basque Country to take the lead and coordinate a strategic response in close collaboration with other European territorial realities’ stakeholders by suggesting the creation of the Basque algorithmic nation for renewing the national community discourse and the state building old narrative employed so far and thus putting at front the strength of the co-operative active response among city-regional businesses, institutions, civic society, academia, and entrepreneurs/activists to ensure (i) the wellbeing and social justice (life), (ii) a sustainable economic model and platform-driven socio-economic alternatives (economy), (iii) a more transparent AI for social good (techno-politics), and ultimately, (iv) further democratic and less dystopic panopticon (democracy). Hence, this article situates itself in the current data policy debate in the EU reinforcing the role city-regions could play in leading data ecosystems under the post-GDPR policy umbrella in the EU particularly by providing cases, projects, and initiatives about technological sovereignty as a result of the collaboration among stakeholders at the local and city-regional level. This policy article is structured in three main sections: (i) Diagnosis, (ii) Intervention, and (iii) Roadmap. COVID-19 krisi pandemikoaren ondorioz Euskal Herrian berriki sortu den egoera aztertzea du xede nagusi artikulu honek. Bereziki, estaturik gabeko nazioa izanik, premiazko esnaldi estrategiko bat beharrezkotzat jotzen du artikuluak erantzun eta begirada tekno-politiko batetik nazioartean bere rola berrirudikatzeko. Europako hiri-eskualdeen mosaikoa anitza izanagatik, konparatiboki Euskal Herrian zentratzen den politiken analisi estrategiko honek, eraldaketa digital, adimen artifiziala (AI), eta datuen gobernantza eta ekosistemek, hiritar eta erakundeak ahalduntzen lagun dezaketeela argudiatzen du balizko bide orri bat aurkeztuz bukaeran. Bide batez, Europako eta nazioarteko hiri, eskualde, eta nazioekin lankidetza transnazionalari irekiera emango ziolarik. Korapilatsuak diren ondorio lazgarriak ugariak izanik Europako hirieskualde askotan, artikulu honek Euskal Herriko eragileak animatzen ditu erantzun bateratu eta estrategiko bat kolektiboki lidera dezaten Europako beste lurraldeetako eragileekin elkarlanean. Zehazki, artikulua, orainarte hegemonikoak izan diren nazio-komunitate eta estatu-eraikuntza bezalako narratibak eguneratzen saiatzen da euskal nazio algoritmiko baten sorkuntza proposatuz. Horretarako beharrezkotzat jotzen du euskal enpresa, erakunde, gizarte zibil, akademia, eta ekintzaile/aktibisten arteko erantzun aktibo eta kooperatibo indartsu bat. Euskal nazio algoritmikoak lau palanka estrategiko izango lituzke aktibaziorako: (i) gizarte ongizatearen bermea eta justizia soziala (bizitza); (ii) eredu ekonomiko jasangarriak eta plataforma bidezko alternatiba sozio-ekonomikoak (ekonomia); (iii) gizarte onurarako adimen artifizial gardenagoa (tekno-politika); eta azkenik, (iv) demokratikoagoa eta ez hain distopikoa den panoptiko bat (demokrazia). Hartara, artikulu hau egun Europar Batasunak (EB) darabilen datu politiken debatean kokatzen da. Debate honen arabera, hiri-eskualdeen rola potentzialki berrindartu liteke, berauek EB-ren post-DBAO arautegiaren pean, datu ekosistemen lider bilakatuko balira. Horretarako, subirautza teknologikoan oinarrituak egon beharko luketen kasu, proiektu, eta egitasmoak burutzea ezinbestekoa litzateke eskualde eta tokian-tokiko eragileen artean. Politiken artikulu hau hiru ataletan banatua dago: (i) Diagnosia, (ii) Interbentzioa, eta (iii) Bide orria.